Mood and context-dependence positive mood increases and negative mood decreases the effects of context on perception. [article]. - Avramova, Yana R.
Five studies show that mood effects context-dependence, such that negative mood promotes attention to a salient target, whereas positive mood enhances attention to both target and context. Judgement of temperature (Study 1), weight (Study 2), and size ( Study 3 and 4) were more strongly affected by the context in a positive than in a negative mood. Moreover, these effects extend to the social domain: When perceiving a target person's emotions, happy people were more influenced by the context than were sad people Study 5). Thus, positive mood enhanced, and negative mood reduced, the magnitude of perceptual context effects. The results suggest that this pattern is not easily explained in terms of effort or depth of processing differences. -- (from the author)
Keywords: Mood; Context dependence; Perceptual context effects; Target judgement